Biocompatibility and biomineralization ability of Bio-C Pulpecto. A histological and immunohistochemical study - Cosme-Silva, Leopoldo [UNESP]; Benetti, Francine [UNESP]; Dal Fabbro, Renan [UNESP]; Gomes Filho, João Eduardo [UNESP]; Sakai, Vivien T.; Cintra, Luciano Tavares Angelo [UNESP]; Alvarez, Nathalia; Ervolino, Edilson [UNESP]; Viola, Naiana V. (My University, 2019)
Aim: To evaluate the inflammatory response, biomineralization and production of osteocalcin (OCN), osteopontin (OPN), and bone sialoprotein (BSP) of a new root filling material for primary teeth (Bio-C Pulpecto) compared to MTA. Design: Polyethylene tubes containing Bio-C Pulpecto, MTA, and empty tubes were implanted into the dorsal connective tissue. After 7, 15, 30, 60, and 90 days, the tubes with surrounding tissue were removed and histologically processed to be analysed using haematoxylin and eosin, von Kossa staining, or no staining for observation under polarized light and immunohistochemistry for the detection of OCN, OPN, and BSP. The Kruskal-Wallis test was used followed by Dunn's test. The significance level was set at 5%. Results: The inflammatory response observed with MTA and Bio-C Pulpecto was more exacerbated until the 15th day and decreased from 30 days on. No significant difference was found between control, MTA, and Bio-C Pulpecto (P > 0.05). Bio-C Pulpecto and MTA showed positivity for von Kossa and birefringent to polarized light. The immunolabelling for OCN, OPN, and BSP was more intense for MTA and Bio-C Pulpecto on days 60 and 90 (P > 0.05). Conclusion: Bio-C Pulpecto was biocompatible, induced biomineralization and was immunopositive for osteogenic markers such as OCN, OPN, and BSP, similarly to MTA.
Keywords: bioactivity; biomineralization; pulpectomy; tooth primary